THE STRATEGIC ROLE OF INTELLECTUAL CAPITAL AND FINANCIAL TECHNOLOGY IN IMPROVING MSME PERFORMANCE IN BANYUMAS REGENCY - Suparno, Chandra; Sulistyandari, Sulistyandari; Novandari, Weni; Widiastuti, Ekaningtyas (Transpublika Publisher, 2024)
The existence of Micro, Small and Medium Enterprises (MSMEs) plays a significant role in contributing to the growth of the Indonesian economy. MSMEs are required to optimize their resources, especially non-physical resources, and utilize existing financial technology (Fintech) in order to be able to compete and develop at all times. Intellectual capital is increasingly recognized as a strategic asset that is considered important for sustainable profits. Business support by utilizing financial technology will improve business performance. The goal of this research is to investigate the impact of intellectual capital and financial technology components on the performance of MSMEs. The resulting sample was 66 respondents who were MSME business actors. The method used was Multiple Regression analysis. The results of the study found that customer capital and structural capital, which are elements of intellectual capital, affect MSME performance, while human capital, social capital, spiritual capital and financial technology do not affect MSME performance. Thus, the elements of intellectual capital owned by MSMEs need to be utilized optimally to achieve competitive advantage and maintain business existence.